2012
DOI: 10.1007/s00167-012-1950-5
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic effectiveness of nerve block in shoulder arthroscopy: comparison between interscalene, suprascapular and axillary nerve blocks

Abstract: Clinical study, Level II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
106
2
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(109 citation statements)
references
References 23 publications
0
106
2
1
Order By: Relevance
“…We justify the relatively short time of catheter use (24 h) with reference to the time course of pain after shoulder surgery [32] and our own clinical experience. A longer duration of catheter use is associated with more administrative demands, more complications (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…We justify the relatively short time of catheter use (24 h) with reference to the time course of pain after shoulder surgery [32] and our own clinical experience. A longer duration of catheter use is associated with more administrative demands, more complications (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The above analysis was performed using Mann-Whitney U test or t test for indifferent samples according to the normality of data to evaluate the differences between the mean values of the group I and group II. the two available ISB methods [5,10,13,24,25]. A randomized controlled trial reported that continuous ISB results in significantly shorter hospital stays than that of single injection ISB [24].…”
Section: Discussionmentioning
confidence: 99%
“…However, the catheter can dislocate during continuous ISB, and patients often become uncomfortable [15]. SSNB is the most widely used method for pain control from arthroscopic shoulder surgery and can be performed under arthroscopy guidance [7,[11][12][13]. ANB has also been adopted for shoulder pain control and is mainly used in combination with SSNB [2,11,13,22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…suprascapular nerve block [5,6], a single interscalene block combined with a continuous intrabursal infusion [7], intraarticular [8,9] or subacromial [10] injection of local anaesthetics, or postoperative intravenous opioid administration with patient-controlled intravenous analgesia [11]. There have been attempts to prolong the duration of sensory block by adding different adjuvants to local anaesthetics used in interscalene brachial plexus block (IBPB), such as dexamethasone [12,13] or dexmedetomidine [14].…”
mentioning
confidence: 99%